Reproduksi Styrotype Politik Gender Dan Framing Media Dalam Debat Pilkada Banten Tahun 2024 - Tubagus Fauzan Kamil; Khalishah Zahra Khairina; Ika Arinia Indriyany (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2026)
Electoral democracy should be a space for contestation for competing ideas and policy programs based on the principle of equality, but in its application, discussions about politics often reproduce gender stereotypes that doubt the legitimacy of women's leadership. The phenomenon that occurred shows in the dynamics of the 2024 Banten Regional Election debate which is able to give rise to statements containing sexist elements and potentially delegitimize women's political authority. This study aims to analyze the reproduction of gender stereotypes in debate discourse and how media framing shapes the construction of meaning and legitimacy of these statements in the public space. The method used in this study is a literature study with a qualitative approach and an analysis of interpretive discourse related to debate broadcasts, online media reports, and existing academic literature related to gender and politics. The results of the study show that sexist speech in debates is not only political rhetoric, but can serve as a mechanism of symbolic violence that reproduces patriarchal stereotypes and can cast doubt on women's leadership capacity. In addition, the media framing that places such statements as political controversies without attributing them. These findings confirm that the quality of democracy is not always determined by electoral mechanisms, but also about the extent to which political space can guarantee legitimacy and equality for women in political discourse.